(untitled) (TSUL LEGAL REPORT, 2026)
In the context of the subject of our article, we find it necessary to clarify the meaning of certain terms related to the use of ICT in the sphere of jurisprudence. Thus, it is essential to differentiate between the terms “electronic judicial process,” “digital court proceedings,” “judicial digitalization,” and “digital justice.” The term “judicial digitalization” refers to the provision of courts with computer resources and technologies that enable information processing. However, it does not fully elucidate the essence and procedure of conducting procedural actions in electronic form.